Multicoated Flexible Indium Tin Oxide Electrodes Fabricated Using Magnetron Sputtering and Arc Plasma Ion Plating for Flexible Perovskite Solar Cells - Seok, Hae-Jun; Lee, Doh-Kwon; Kim, Han-Ki (American Chemical Society, 2024)
High-performance flexible Sn-doped In2O3 (indium tin oxide, ITO) electrodes were fabricated using a multicoating process on colorless polyimide (CPI) substrates for flexible perovskite solar cells (FPSCs). The effects of different coating sequences on the electrical, optical, and mechanical properties of the flexible ITO electrodes were thoroughly investigated after preparing them with direct-current magnetron sputtering (DMS) and arc plasma ion plating (APIP). Although both the sputtered ITO (SITO)/arc ion-plated ITO (AITO) film and the AITO/SITO film showed similarly low sheet resistance (18.69-25.29 Omega/sq) and high optical transmittance (94.96-96.85%), the coating sequence significantly affected the mechanical flexibility of the multicoated ITO films. The 120 nm-thick SITO/AITO electrode exhibited small outer and inner critical bending radii (3 mm and 3 mm, respectively) compared to the AITO/SITO electrode (4 and 5 mm, respectively). Owing to better adhesion of the arc-ion-plated ITO bottom layer and the amorphous structure of the top SITO layer, the SITO/AITO electrode exhibited excellent mechanical flexibility and durability. In addition, an FPSC using the SITO/AITO electrode achieved a higher power conversion efficiency (15.09%) than that with the AITO/SITO electrode (13.22%). This improvement was attributed to its high transmittance, low sheet resistance, smooth surface morphology, and enhanced hole collection efficiency. These findings highlight the efficacy of the combined DMS and APIP multicoating process for fabricating high-quality flexible ITO electrodes for high-performance FPSCs.